Developing forecasting model for future pandemic applications based on COVID-19 data 2020-2022 - Nurul Hila Zainuddin (Tanjung Malim, 2023)
Developing forecasting model for future pandemic applications based on COVID-19 data 2020-2022 by Nurul Hila Zainuddin